Planning for drought in MENA - International Water Management Institute (International Water Management Institute, 2022)
The blog is about the work of the International Water Management Institute (IWMI) partnering with the governments of Jordan, Lebanon and Morocco to develop drought action plans (DAPs) as part of its broader efforts to support them to prepare for, mitigate, and respond to the worst impacts of drought. The DAPs identified actions to reduce drought risk, and their development included a process to identify and analyze the root causes of specific drought impacts.